The meaning of traditional poetic school in B. Otepuly`s works (Eurasian Journal of Philology Science and Education, 2015)
The tradition of poetic schools in Kazaly and Aral regions which is closely connected with regularities of history of development of the Kazakh literature as a whole is traced in this article. Baynazar Otepuly's creativity living in thecalled region, reflects process of formation of a new society and it is a spiritual treasury of national literature. Authors of the article gave the systemic description of the creative environment made by poetic schools. In this work it is proved that Baynazar Otepuly left a peculiar handwriting in the history of literature. Poet’s work is considered in a context of poetry tradition. Akyn’s poetry will be developed and further on an equal basis with the Kazakh poetry.
Keywords: national wealth; national characteristics; folklore; National poetry; national character; style; classical literature; tradition.